VD_FINDINFO HC / 2016 / 156 vom 12. Januar 2016 - VD Tribunal cantonal (2016)
FARDEAU DE LA PREUVE, COMMUNAUTÉ HÉRÉDITAIRE, CONTRAT FIDUCIAIRE | 474 CC, 604 al. 1 CC, 400 CO, 401 CO, 405 CO, 170 CPC, 404 al. 1 CPC (CH)